Гранулювання дисперсних матеріалів в умовах контактного тертя з робочими органами машин - Штефан, Євгеній Васильович; Риндюк, Дмитро Вікторович (НТУ "ХПІ", 2014)
В роботі розглянуто проблему гранулювання дисперсних матеріалів в умовах контактного тертя з робочими органами вузла пресування гранулятора. Досліджено вплив шорсткості контактної поверхні на коефіцієнт тертя ковзання при різних швидкостях руху дисперсних матеріалів (стружка сосни та лушпиння соняшника) по сталевій поверхні в каналі формуючої головки. He paper’s topic is connected with the actual problem of solid bio fuel manufacturing. The organic disperse material compaction technologies is observed. The article is devoted to creation of scientific bases of designing both improvement of processes and equipment of solid bio fuel production. It will provide an opportunity of rational constructive–technological design data choice of the equipment and modes of its operation. This paper considers the problem of disperse materials granulation under contact with friction at working surfaces in the pressing node. One of the main parameters that have great influence on granules shaping features is friction coefficient between extruders working surfaces and disperses materials. The experimental method of friction coefficient determination is presented. The steel contact surface roughness influence on friction coefficient with different speed moving of disperse material (pine shavings and sunflower husks) is studied. The experimental results statistic analyze (regressed methods) gave it’s possible to obtain analytic equation for friction coefficient calculation.
Keywords: тверде біопаливо; solid biofuel; коефіцієнт тертя ковзання; coefficient of friction; шорсткість; roughness; екструзія; extrusion; гранула; granule; кафедра машин і апаратів харчових та фармацевтичних виробництв